Working guide to vapor-liquid phase equilibria calculations - Ahmed, Tarek H., 1946- (Gulf Professional, 2009)
The Vapor-Liquid Phase Equilibria process is widely used for the distillation of petroleum and natural gas before it is transported to the refinery for final possessing. While simulation programs can provide some answers, the quality of the results obtained with these programs depends on the quality of the model parameters. Parameters which are derived using the calculations methods find in this book. Includes explanations of formulas; Step by step calculations; Provides examples and solutions.